2018
DOI: 10.1152/physiolgenomics.00006.2018
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor kinase-2-deficient mice are protected from dextran sodium sulfate-induced acute colitis

Abstract: G protein-coupled receptor kinase 2 (GRK2) is a serine/threonine kinase and plays a key role in different disease processes. Previously, we showed that GRK2 knockdown enhances wound healing in colonic epithelial cells. Therefore, we hypothesized that ablation of GRK2 would protect mice from dextran sodium sulfate (DSS)-induced acute colitis. To test this, we administered DSS to wild-type (GRK2) and GRK2 heterozygous (GRK) mice in their drinking water for 7 days. As predicted, GRK2 mice were protected from coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…All these data indicate that GRK2 plays a key role in inflammatory immune disease. A previous study showed that GRK2 deficiency protected mice from DSS‐induced colitis 16 . The current study highlights the important role of GRK2 in mediating colitis and suggests that GRK2 might be a potential drug target for IBD.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…All these data indicate that GRK2 plays a key role in inflammatory immune disease. A previous study showed that GRK2 deficiency protected mice from DSS‐induced colitis 16 . The current study highlights the important role of GRK2 in mediating colitis and suggests that GRK2 might be a potential drug target for IBD.…”
Section: Discussionsupporting
confidence: 59%
“…Changes in GRK2 levels and functions play a key role in the progression of certain diseases 53,54 . The GRK2 level was related to the degree of inflammation in UC patients and animal disease models 16,55 . All these data indicate that GRK2 plays a key role in inflammatory immune disease.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations